Homogeneous and Heterogeneous Photo-Fenton-Based Photocatalytic Techniques for the Degradation of Nile Blue Dye - Georgia Papadopoulou; Eleni Evgenidou; Dimitra Lambropoulou (Applied Sciences, 2025)
In this study, the degradation of Nile Blue dye was investigated using homogeneous and heterogeneous photocatalytic methods based on the photo-Fenton reaction. More specifically, for homogeneous photocatalysis, the classical photo-Fenton (UV/Fe2+/H2O2) and modified photo-Fenton-like (UV/Fe2+/S2O82−) systems were studied, while for heterogeneous photocatalysis, a commercial MOF catalyst, Basolite F300, and a natural ferrous mineral, geothite, were employed. Various parameters—including the concentrations of the oxidant and catalyst, UV radiation, and pH—were investigated to determine their influence on the reaction rate. In homogeneous systems, an increase in iron concentration led to an enhanced degradation rate of the target compound. Similarly, increasing the oxidant concentration accelerated the reaction rate up to an optimal level, beyond which radical scavenging effects were observed, reducing the overall efficiency. In contrast, heterogeneous systems exhibited negligible degradation in the absence of an oxidant; however, the addition of oxidants significantly improved the process efficiency. Among the tested processes, homogeneous techniques demonstrated a superior efficiency, with the conventional photo-Fenton process achieving complete mineralization within three hours. Kinetic analysis revealed pseudo-first-order behavior, with rate constants ranging from 0.012 to 0.688 min−1 and correlation coefficients (R2) consistently above 0.90, confirming the reliability of the applied model under various experimental conditions. Nevertheless, heterogeneous techniques, despite their lower degradation rates, also achieved high removal efficiencies while offering the advantage of operating at a neutral pH without the need for acidification.